Kandungan dan Kecernaan Bahan Kering dan Bahan Organik Lamtoro Tarramba (Leucaena leucocephala cv. Tarramba) yang Diberi Pupuk Amazing Bio Growth Tablet dengan Level yang Berbeda Secara In Vitro: Content and Digestibility of Dry Matter and Organic Matter Lamtoro Tarramba (Leucaena leucocephala cv. Tarramba) Given Fertilizer Amazing Bio Growth Tablets With Different Level In Vitro - Rio Anderias Sasongko Sakan; Twenfosel Ocsierly Dami Dato; Marthen Yunus (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of the use of organic fertilizers Amazing Bio Growth tablet with different levels of content and digestibility in vitro forage of lamtoro tarramba. The experimental design used in this study was a completely randomized design, consisting of 5 treatments with 3 replications. Such treatment is: R₀= without fertilizer ABG tablet (control), R₁= ABG tablets 10g, R₂= ABG tablet 20g, R₃ = ABG tablet 30g, and R₄ = ABG tablet 40g. The variables observed were: content and digestibility of dry matter and organic matter in vitro. The results showed the mean dry matter content(%) : R₀ (88.53±0.22); R₁ (88.77±0.60); R₂ (88.86±0.25); R₃ (88.91±1.47); R₄ (89.64±0.74); organic matter content: R₀ (80.51±0.10); R₁ (80.695±0.47); R₂ (81.60±0.33); R₃ (81.69±1.29); R₄ (81.98±0.46); digestibility in vitro of dry matter (%): R₀ (71.39±0.72); R₁ (72.24±0.09); R₂ (72.43±1.15); R₃ (73.91±2.26); R₄ (74.57±1.12); and digestibility in vitro of organic matter (%): R₀ (66.15±1.63); R₁ (66.18±1.88); R₂ (67.70±0.86); R₃ (67.91±2.70); R₄ (70.35±0.49). The results of statistical analysis showed that the treatment of ABG tablet organic fertilizer had no significant effect (P> 0.05) on the content and digestibility in vitro of dry matter and organic matter. It was concluded that the use of ABG tablet organic fertilizer was 40g significantly. can reduce the content of dry matter and organic matter so that it gives a real response to the digestibility in vitro of organic matter and dry matter in tarramba lamtoro forage. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan pupuk organik Amazing Bio Growth tablet dengan level yang berbeda terhadap kandungan dan kecernaan in vitro bahan kering dan bahan organic hijauan lamtoro tarramba. Rancangan percobaan yang digunakan adalah rancangan acak lengkap, terdiri dari 5 perlakuan dengan 3 ulangan, yakni: R₀ = tanpa pupuk ABG tablet (kontrol); R₁ = ABG tablet 10g ; R₂ = ABG tablet 20g ; R₃ = ABG tablet 30g ; dan R₄ = ABG tablet 40g. Variabel yang diamati adalah: kandungan dan kecernaan bahan kering dan bahan organik in vitro. Hasil penelitian menunjukkan bahwa rataan kandungan bahan kering (%): R₀ (88,53± 0,21); R₁ (88,77± 0,60); R₂ (88,86± 0,25); R₃ (88,91± 1,46); R₄ (89,64± 0,73); kandungan bahan organic (%): R₀ (80,51±0,11); R₁ (80,69± 0,47); R₂ (81,60± 0,33); R₃ (81,69±1,29); R₄ (81,98±0,46); kecernaan in vitro bahan kering (%): R₀ (71,39±0,72); R₁ (72,24±0,08); R₂ (72,43±1,14); R₃ (73,91±2,25); R₄ (74,57±1,11); dan kecernaan in vitro bahan organic (%): R₀ (66,15±1,63); R₁ (66,18±1,87); R₂ (67,70±0,85); R₃ (67,91±2,70); R₄ (70,35±0,49). Hasil analisis statistik menunjukkan bahwa perlakuan penggunaan pupuk organik ABG tablet berpengaruh tidak nyata (P>0,05) terhadap kandungan dan kecernaan in vitro bahan kering dan bahan organik, Disimpulkan bahwa penggunaan pupuk organik ABG tablet hingga level 40g belum memberikan respon yang nyata terhadap kandungan dan kecernaan in vitro bahan kering dan bahan organik pada hijauan lamtoro tarramba.